The essence of vocational guidance of secondary school students and the integration of didactic resources in the classroom (on the case of teaching the subject of technology) - D.A. Makhkamova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses career guidance in the lessons of the subject "Technology" in a secondary school based on integrative learning using didactic resources.